PERAN BUDAYA ORGANISASI, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Reka Mawaddah Harisandi; M. Farid Wajdi (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is to analyze the role of organizational culture, work environment and work discipline on employee performance. This research method is quantitative. The population of this study is all employees at Bank Bri Kanca Sukoharjo Kota, Bank Bri Surakarta City Center, Bank Bri Unit Serengan, Bank Bri Kc Solo Slamet Riyadi and Bank Bri Kc Solo Sudirman. The sample technique used in this study was purposive sampling. The number of samples in this study was 64 respondents. The type of data used in this study is primary data.  Data collection techniques using questionnaires. The data analysis technique in this study uses a Partial Least Square (PLS)-based SEM structural equation model. The result of this study is that Organizational Culture has a positive and significant influence on Employee Performance. The Work Environment has a positive and significant influence on Employee Performance. Work Discipline has a positive and significant influence on Employee Performance